2019
DOI: 10.1139/cjz-2018-0289
|View full text |Cite
|
Sign up to set email alerts
|

A molecular approach to identifying the relationship between resource use and availability in Eurasian otters (Lutra lutra)

Abstract: In South Korea, the Eurasian otter (Lutra lutra (Linnaeus, 1758)), a semi-aquatic carnivore, is found mainly in lower order streams that tend to have a low abundance of preferred prey fish species. To investigate the relationship between resource use and availability, we used DNA barcoding to identify otter diet items in 24 otter spraints (faeces) from 16 sites along the Nakdong River basin from 4 to 6 June 2014. At these sites fish availability was assessed using scoop nets and casting nets. Fish formed the b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 37 publications
1
13
0
Order By: Relevance
“…Previous studies [3133] demonstrated that 12S rRNA gene sequences provide accurate identification of most of fishes including teleosts at species level, highlighting the 12S rRNA gene as an ideal marker for diet analyses of Eurasian otters. Additionally, we confirmed that fish species identified in this study are in agreements with fish species detected from spraints by a previous study [10] and spatial distributions of their habitats in Korea [34].…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Previous studies [3133] demonstrated that 12S rRNA gene sequences provide accurate identification of most of fishes including teleosts at species level, highlighting the 12S rRNA gene as an ideal marker for diet analyses of Eurasian otters. Additionally, we confirmed that fish species identified in this study are in agreements with fish species detected from spraints by a previous study [10] and spatial distributions of their habitats in Korea [34].…”
Section: Discussionsupporting
confidence: 91%
“…Similar to the previous findings [35–37], the majority of the detected fishes belonged to the family Cyprinidae (Fig 4) among which Carassius auratus (crucian carp) was the most dominant species detected across all spraints (Fig 5). A previous study also reported that Cyprinidae was the most dominant diet by the Eurasian otters along a river basin in South Korea [10]. C .…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…Could this be an evidence of dispersal of these otters along the coastal sea line? It is reported that the Eurasian otter, thanks to its plasticity, may live along the sea coast (Elmhirst, 1938;Kruuk & Hewson, 1978;Chanin, 1985;Panzacchi et al, 2011) and can expand its home range to include salt water when suitable prey fish are scarce (Crowley et al, 2013;Lanszki et al, 2014;Mulville, 2015;Hong et al, 2019), like other medium-sized carnivores (Doncaster & Woodroffe, 1993;Eide et al, 2004), even though it requires access to fresh water for the cleaning of the fur (Kruuk & Balharry, 1990;Beja, 1996). Furthermore, many reports from zoophilic enthusiasts (on social networks) would corroborate this hypothesis, but further investigations are necessary.…”
Section: Population Genetic Structurementioning
confidence: 99%